On a record of cow shark’ tooth (Neoselachii, Hexanchidae) from the Upper Cretaceous of Saratov Volga region - Popov, Evgeniy Valerievich; Lopyrev, Vladimir Alekseevich; Seltzer, Vladimir Borukhovich (Известия Саратовского университета. Новая серия: Серия Науки о Земле)
The discovery of a tooth of the cow shark Hexanchus microdon (Ag., 1835) from carbonate deposits of the Karsun Formation in the ‘Krasny Oktyabr’ quarry (Volsk, Saratov Volga River Right Bank) is described. Based on the associated foraminifera complex, the stratigraphic position of the find was determined as Lower Maastrichtian, benthic foraminifera LC20 Falsoplanulina multipunctata Zone. It was calculated that the individual size of the described shark species H. microdon was 153–166 cm. This is the first record of the species in the region and in the Upper Cretaceous deposits of Russian Plate, which expands the paleobiogeographic range of the species.